ANALISIS PERAN SUB SEKTOR PERTANIAN DALAM PEMBANGUNAN PERTNAIAN INDONESIA - Muhammad Fadhil; Cut Zakia Rizki (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
AbstractThis reseach have pusposte to analyze Share from agliculture subs sector, and to predict trend share. Data used in this reseach is from indoneisa GDP in 2010-2018. Model that used in this research is share function and least square method. result from this research show that some of agliculture sub sector experience share decline trend share analyze show result that every sector that experiend declince in share will experience lose too in the next five years. From this research goverment are expected to make policy that include citizen from the country to participate to make that policy have good impact.Keywords : aglicultur development, share and trend share agliculture analyze